Translating early Soviet fiction: the impact of source text foreignisation on translation theory and practice: a case study of Evgenii Zamiatin and Andrei Platonov - Martin, Kathryn (2019)
This thesis investigates the translation challenges created by early Soviet era Russian source texts that employ non-standard language for literary effects. It employs a framework of Soviet linguistic theories as well as translation theory to analyse Evgenii Zamiatin’s 1918 novel Ostrovitiane and his 1922 work My, as well as Andrei Platonov’s 1930 text Kotlovan. By providing a diachronic, comparative analysis of different translations of these texts into English, this thesis discusses the suitability of equivalence-based approaches to translation and proposes that non-standard language use in literary texts requires translators to approach foreignness as a function of the source text, not as a comparative status of otherness between source and target cultures. The thesis begins by introducing the context of the development of the Russian language, as well as the field of Soviet linguistics, in the 1917-34 period. By highlighting the developing field of sociolinguistics in Soviet Russia, as well as examining the ways that this was used by the state to direct language development, Chapter one sets out the linguistic standards which are manipulated by Platonov and Zamiatin in their texts. In Chapter two, it turns to Eugene Nida’s dynamic equivalence, and outlines the ways in which its principal demands of producing language that is ‘natural’ and ‘idiomatic’ as well as creating equivalence of effect on target text readers are challenged by non-standard language use in texts. Furthermore, it offers a new contribution to the field of translation studies, by challenging Lawrence Venuti’s theory of foreignization, by arguing against the current dominant view point of foreignness as a function of translation rather than as an effect created in the source text through non-standard language use that deviates from current norms. The theoretical frames which have been established in Chapters one and two are then used as the framework against which the language of the source text and translations of the novels which make up the corpus of the thesis are subsequently analysed in Chapters four, five and six. The thesis analyses a variety of examples of the manipulation of language, from the use of occasionalisms by Zamiatin in Ostrovitiane, the use of Soviet jingoism in My, and the manipulation of cultural discussions of language in Platonov’s Kotlovan, among others to demonstrate the ways in which these texts create tensions between Nida’s equivalence principles, as well as challenging Venuti’s foreignization principles. As an interdisciplinary project, this thesis contributes to a number of academic discourses. By connecting Nida’s 1964 theory with more contemporary areas of research in translation studies such as the study of paratext, and retranslation theory, it offers new perspectives on the effects of dynamic equivalence on translation practice, as well as the way that it can affect the ways that texts are read. Furthermore, by offering a different approach to the foreign in the text, it contributes to the challenges that have already been made in the field to Venuti’s translation theory. In so doing, it offers an approach to foreignness in source text whose results are pertinent to a wide range of literary texts and contexts in translation.